2019
DOI: 10.1039/c9ta04325j
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional lead-free iodide-based hybrid double perovskites: crystal growth, thin-film preparation and photocurrent responses

Abstract: Herein, lead-free layered iodide double perovskites (C6H16N2)2MBiI8 (M = Ag/Cu) were synthesized, which showed typical semiconducting properties and obvious photocurrent response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 33 publications
7
107
1
Order By: Relevance
“…However, the band gap of Bi‐based perovskites (>1.8 eV) is still far higher than the ideal band gap of solar cells (1.3–1.4 eV), unless toxic Tl 3+ is doped into Cs 2 AgBiBr 6 . In view of these features of lead‐halide‐based perovskites, Bi‐based perovskites materials with 2 D and ideal 3 D metal–halogen frameworks might be more efficient . It is highly preferable to maintain the 3 D perovskite structure by replacing Pb with low‐toxicity metal cations .…”
Section: Introductionmentioning
confidence: 68%
“…However, the band gap of Bi‐based perovskites (>1.8 eV) is still far higher than the ideal band gap of solar cells (1.3–1.4 eV), unless toxic Tl 3+ is doped into Cs 2 AgBiBr 6 . In view of these features of lead‐halide‐based perovskites, Bi‐based perovskites materials with 2 D and ideal 3 D metal–halogen frameworks might be more efficient . It is highly preferable to maintain the 3 D perovskite structure by replacing Pb with low‐toxicity metal cations .…”
Section: Introductionmentioning
confidence: 68%
“…This result showed that 2D halide double perovskites could be optically activated by increasing the pressure. In another approach, two new 2D double perovskites (C6H16N2)2AgBiI8•H2O and (C6H16N2)2CuBiI8•0.5H2O were synthesized [88]. These perovskites had bandgaps of 1.93 eV and 1.68 eV, respectively.…”
Section: D Halide Double Perovskitesmentioning
confidence: 99%
“…Recently, seven new double perovskites, namely, PA4AgInCl8, PA4AgBiBr8, and PA4AgInBr8,where PA stands for propyl-ammonium, and OCA4AgBiBr8, BDA2AgBiBr8, PA2CsAgBiBr7, and PA2CsAgIn0.5Bi0.5Br7, where OCA stands for octyl-ammonium and BDA for 1,4butanediammonium, have been synthesized and characterized, as shown in Figure 18 [83]. In another approach, two new 2D double perovskites (C6H16N2)2AgBiI8•H2O and (C6H16N2)2CuBiI8•0.5H2O were synthesized [88]. These perovskites had bandgaps of 1.93 eV and 1.68 eV, respectively.…”
Section: D Halide Double Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations